USING AUDIO STORYTELLING MEDIA TO IMPROVE STUDENT UNDERSTANDING - novaseroja seroja (Teaching and General Education Studies, 2026)
This research is motivated by the low level of student understanding in the learning process caused by the use of less varied learning media. One medium that can be used to improve student understanding is audio storytelling, a learning medium that conveys material through stories in audio form. This study aims to determine the effect of using audio storytelling on student understanding in learning. The research method used is a quantitative approach with data collection techniques in the form of tests, observations, and documentation. The results show that the use of audio storytelling can improve student understanding of the learning material. Thus, audio storytelling can be an effective alternative learning medium to create more interesting and meaningful learning for students.